Too many policy options, not enough diversity? A typology of tourism policy tools - Costa, Cláudia S. (2020)
The design of a typology of policy tools specifically aimed at tourism policy represents the main goal and the original contribution of this article. Based on the theory of market failures and the tools of government approach, we extend Weimer and Vining’s original typology of public policies to the field of tourism by relying on an empirical analysis of tourism policy tools adopted by local governments in Portugal. The results suggest the existence of specific situations requiring the enlargement of Weimer and Vining typology. The ultimate goal is to contribute to research and practice in the field of tourism policy and management by providing both scholars and decision-makers with a policy toolbox, which can be useful to tackle policy problems in tourism markets.